Reconstruction of The Settlement of Misdemeanor Crimes by The Prosecutor's Office Through Restorative Justice - Romie, Romie; Hasibuan, Fauzie Yusuf; Kristiawanto, Kristiawanto (Advances In Social Humanities Research, 2025)
Narcotics abuse remains a major challenge within Indonesia's criminal justice system, where a punitive approach emphasizing imprisonment still dominates over rehabilitation strategies. Although Restorative Justice offers a more humane alternative by prioritizing recovery and social reintegration, its implementation faces various obstacles, including regulatory inconsistencies, lack of rehabilitation facilities, limited understanding among law enforcement officials, and persistent social stigma against abusers. This study aims to analyze the effectiveness of Restorative Justice in narcotics abuse cases and propose regulatory reconstruction to strengthen rehabilitation-oriented resolutions. Employing a normative juridical method combined with an empirical approach, the research examines relevant legislation, court decisions, and field practices. The findings reveal a gap between regulatory frameworks, such as Law No. 35/2009, and progressive policies like Attorney General Regulation No. 18/2021, resulting in uneven application of Restorative Justice. Furthermore, limited infrastructure and social perceptions hamper recovery efforts. This study recommends harmonizing narcotics regulations, enhancing coordination among law enforcement agencies, expanding rehabilitation facilities, providing specialized training on restorative approaches, and promoting public education to reduce stigma. With comprehensive reforms, Indonesia’s criminal justice system can become more effective, balancing legal certainty with the principles of substantive justice, and offering a humane solution to narcotics abuse through a recovery-oriented model.